Transgenic Plants: Review on Risks and Benefits in the Environment of Developing Countries - Shrivastava, Umesh Prasad (Academic Voices: A Multidisciplinary Journal, 2011)
Various transgenic plants have been produced employing various techniques. These plants perform interaction among other organisms the agro-environment. But, cultivation of these plants is a matter of debate. Various questions on risk factors have been raised by many authors, e.g. problems related consequences of gene escape, adverse impact on biodiversity, natural enemies, pollinators, soil organisms, decomposers and various non target organisms. On the other hand, various supporters give emphasis in the favour of transgenic plants praising its benefits, e.g. reduced environmental impact from pesticides and insecticide, increased yield, soil conservation, phytoremediation etc. Critical analysis of this controversy is the main concern of this present mini review. Also, an attempt has been made to describe the potential impact of transgenic plants in developing countries. Keywords Transgenic plants, genetically modified organisms, risks, benefits, developing countries DOI: http://dx.doi.org/10.3126/av.v1i0.5315 Academic Voices 2011; 1: 84-93